Sequential injection spectrophotometric system for evaluation of mushroom tyrosinase-inhibitory activity - Moonrungsee N. (2014)
A sequential injection (SI) spectrophotometric method with absorbance detection at 475 nm has been developed for evaluating activity of some compounds on an inhibition of the mushroom tyrosinase. The method involved a reaction of 3,4-dihydroxyphenylalanine (l-DOPA) and mushroom tyrosinase to form the o-dopaquinone. The decrease of the o-dopaquinone was related to an increase of tyrosinase-inhibitory activity. Under the optimum conditions (concentration and volume of l-DOPA and mushroom tyrosinase of 2.0 mM, 60 μL and 142 U mL -1, 15 μL, respectively), some antioxidant compounds were examined for the tyrosinase-inhibitory activity. A batch enzymatic assay of tyrosinase-inhibitory activity was applied as the reference method for comparison. The results of IC 50 values obtained from the proposed method and the batch method were correlated well, with r 2 of 0.969. The SIA provides higher precision and degrees of automation, consumes smaller amounts of chemicals and it is simpler and faster than the batch method. © 2012 Elsevier B.V. All rights reserved.